2001
DOI: 10.1179/eja.2001.4.3.385
|View full text |Cite
|
Sign up to set email alerts
|

High-tech in the middle Palaeolithic: Neandertal-manufactured pitch identified

Abstract: Any new knowledge that goes beyond the stone tools and techniques used in the Palaeolithic and Mesolithic is most significant as it reveals the cultural and technical capabilities of the people living in these periods. In 1963, two pitch finds were discovered in a lignite open-mining pit in the northern foothills of the Harz Mountains, in a layer the geological age of which was dated as being older than 80,000 years. The great significance of these finds was therefore immediately apparent. One of the finds sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(87 citation statements)
references
References 6 publications
2
84
1
Order By: Relevance
“…The German site of Königsaue, for instance, yielded unique evidence for the mastering of complex fire technology by Micoquian (late Middle Paleolithic) Neandertals. Chemical analysis of two fragments of birch bark pitch used for the hafting of stone knives and directly dated to > 44 ka 14 C BP showed that the pitch had been produced through a severalhour-long smoldering process requiring a strict manufacture protocol, i.e., under exclusion of oxygen and at tightly controlled temperatures (between 340 and 400 • C) (Koller et al, 2001). The Königsaue pitch is the first artificial raw material in the history of humankind, and this unique example of Pleistocene high-tech clearly could not have been developed, transmitted, and maintained in the absence of abstract thinking and language as we know them; it certainly requires the enhanced working memory whose acquisition, according to Coolidge and Wynn (2005), is the hallmark of modern cognition.…”
Section: Resultsmentioning
confidence: 99%
“…The German site of Königsaue, for instance, yielded unique evidence for the mastering of complex fire technology by Micoquian (late Middle Paleolithic) Neandertals. Chemical analysis of two fragments of birch bark pitch used for the hafting of stone knives and directly dated to > 44 ka 14 C BP showed that the pitch had been produced through a severalhour-long smoldering process requiring a strict manufacture protocol, i.e., under exclusion of oxygen and at tightly controlled temperatures (between 340 and 400 • C) (Koller et al, 2001). The Königsaue pitch is the first artificial raw material in the history of humankind, and this unique example of Pleistocene high-tech clearly could not have been developed, transmitted, and maintained in the absence of abstract thinking and language as we know them; it certainly requires the enhanced working memory whose acquisition, according to Coolidge and Wynn (2005), is the hallmark of modern cognition.…”
Section: Resultsmentioning
confidence: 99%
“…But they do not confirm that red ochre functioned exclusively in symbolic contexts, and do not explain how the symbolic use of ochre arose (d 'Errico et al, 2010, p. 4). The exploitation of ochre of variable colour and geological origin is not limited to H. sapiens (see for example Koller et al, 2001;Grünberg, 2002;Soressi and d'Errico, 2007;Zilhão et al, 2010 for ochre exploitation by H. neanderthalensis) and its use does not reflect a 'quantum leap' from archaic to 'modern' patterns of behaviour (Conard, 2005, p. 310). The habitual exploitation of red ochres (see Watts (2002Watts ( , 2009) for detailed explanations) may however represent a species-specific behavioural trait for H. sapiens (Henshilwood et al, 2009, p. 3;Watts, 2010, p. 393).…”
Section: Archaeological Ochrementioning
confidence: 97%
“…Usually analytical procedures based on gas chromatography-mass spectrometry following solvent extraction and trimetylsilylation have been used to identify birch bark tar, owing to a series of characteristic triterpenoid markers with a lupane skeleton [4,[6][7][8]10,11,13,14]. Betulin and lupeol together with low amounts of lupenone, betulone and betulinic acid are known to be characteristic of birch bark [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Tar from Betulaceae bark has been found on arrowheads and flint tools from the prehistoric age and the tar has been interpreted as a residue of the original adhesives [3][4][5][6][7][8][9][10][11]. A chemical study of amorphous materials recovered from flint artefacts found in Campitello (Arezzo, Italy) revealed that birch bark tar was already being produced in the early-Palaeolithic period, and this represents the oldest finding of birch bark tar known until now [9,12].…”
Section: Introductionmentioning
confidence: 99%